Comparative demographic and clinicopathological study on the behavior of mammary carcinoma in three Iraqi governorates (Baghdad, Hilla and Karbala) - Al-Alwan, Nada A. S.; Al-Rufaee, Farah L. R. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Breast cancer is the most common malignant tumor in women worldwide. In Iraq, there is a tendency for this disease to be diagnosed in younger ages, at advanced stages with a prevalence of more aggressive tumor behavior. Patients and Methods: The study included a total of 216 women with breast lumps and proven breast cancer who visited the Main Referral Training Center for Early Detection of Breast Tumors in the Medical City Teaching Hospital in Baghdad (85 patients) and the Specialized Clinics belonging to the major hospitals of Hilla (62 patients) and Karbala (69 patients) complaining of apparent breast lumps. Results: 31% of patients was in the age category (40-49 years), 38.4% of patients whose highest education within the primary school level, 36.4% of patients had history of lactation, 52.3% of total had started menstruation at the age (10-12 years), 85% of patients had negative history of oral contraceptive pills consumption, Ki-67 tumor marker was demonstrated in 62.5% of total with highest frequency of expression was displayed in Baghdad and in relation with grade II. Conclusion: Significant differences among the three Iraqi governorates were noted with respect to patient’s age, educational status, history of breast feeding, age at menarche and history of oral contraceptive pills consumption. Higher Ki-67 nuclear expressions were demonstrated among patients from Baghdad. There was a direct significant relationship between Ki-67 nuclear expression and the nuclear staining intensity with tumor grades.